1995
DOI: 10.1524/ract.1995.68.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Neptunium(V) on Various Iron Oxides and Hydrous Iron Oxides

Abstract: In order to see the effect of crystallinity and surface conditions of various oxides and hydrous oxides on the sorption of metal ions, the sorption of tracer concentration (~10" 12 M) of neptunium(V) on naturally-occurring iron minerals (goethite, hematite, magnetite), synthetic iron oxide powders (a-Fe 2 0 3 and Fe 3 0 4 ) and laboratory-prepared hydrous iron oxides (a-FeOOH and amorphous hydrous iron oxide) was studied as a function of pH. The sorption was found to strongly depend on the crystal structure as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 4 publications
3
24
0
Order By: Relevance
“…The sorption behavior of Np(V) to hematite under aerobic and anaerobic conditions was not noticeably different, because the Np(V) species onto hematite was not reduced [110]. The sorption was found to strongly depend on the type of FHOs: goethite > ferrihydrite > hematite, magnetite [114]. More recently, Tinnacher et al [115] investigated kinetics of Np(V) sorption and desorption on goethite using experimental and modeling methods.…”
Section: Distribution Coefficient and Sorption Percentagementioning
confidence: 99%
“…The sorption behavior of Np(V) to hematite under aerobic and anaerobic conditions was not noticeably different, because the Np(V) species onto hematite was not reduced [110]. The sorption was found to strongly depend on the type of FHOs: goethite > ferrihydrite > hematite, magnetite [114]. More recently, Tinnacher et al [115] investigated kinetics of Np(V) sorption and desorption on goethite using experimental and modeling methods.…”
Section: Distribution Coefficient and Sorption Percentagementioning
confidence: 99%
“…A number of studies of neptunium sorption on geological phases have been carried out, in particular on iron oxides and hydrous oxide materials (12)(13)(14). Using XAS, Combes et al (13) showed that sorption of Np(V) onto goethite involved inner-sphere complexation of the NpO2 + unit to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…It possesses high sorption capabilities for heavy elements, like uranium [116][117][118][119][120][121], plutonium [122,123], neptunium [123,124], americium [125] or strontium [126,127]. Additionally, under reducing conditions, it can fix hydrogen while transforming to magnetite (Fe 3 O 4 ).…”
Section: Haematitementioning
confidence: 99%